Clear-Cell Sarcoma of Tendons and Aponeuroses Studied by Immunoscintigraphy - Rodrigues, Margarida; Vieira, Rosário M.; Marques, A.; Almeida, Odete; Costa, Oliveira (Nuklearmedizin - NuclearMedicine, 1995)
Clear-cell sarcoma is a rare tumor that arises in association with tendons and aponeuroses. Although it shares with malignant melanoma several histologic and ultrastructural features, it has a clinical course different from that of conventional melanomas. A case of clear-cell sarcoma studied by immunoscintigraphy with 99mTc-labeled F(ab’)2 fragments of the monoclonal antibody 225.28 S is reported.Das clear cell-Sarkom ist ein seltener Tumor, der von der Vereinigung von Sehnen und Aponeurosen stammt. Obwohl er mit dem malignen Melanom histologische und ultrastrukturelle Ähnlichkeiten aufweist, stimmt sein klinischer Verlauf mit jenem konventioneller Melanome nicht überein. Ein Fall eines clear cell-Sarkoms wurde mittels Immunszintigraphie mit 99mTc-markierten monoklonalen Antikörper 225.28S F(ab’)2-Fragmenten diagnostiziert.
Keywords: Clear-cell sarcoma; malignant melanoma; immunoscintigraphy; F(ab’)2 MoAb 225.28S